A general ant colony model to solve combinatorial optimization problems - Aguilar, José (Revista Colombiana de Computación, 2001)
An Ants System is an artificial system based on the behavior of real ant colonies, which is used to solve combinatorial problems. Keywords: Combinatorial Optimization Problem,AntSystem, the Graph Partitioning and The Traveling Salesman Problems.